Mejoramiento genético. Mejoramiento de caracteres. Entomología - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1986)
Evaluations of host-plant resistance to Empoasca kraemeri, bruchids, and Apion godmani continued in 1985. Leafhopper-resistant breeding lines from 5 cycles were evaluated in the field to determine whether advances in overall resistance levels had been obtained over cycles of selection. The identification of wild Phaseolus vulgaris germplasm from Mexico with high levels of resistance to bruchids formed the bases of a bruchid breeding program, resulting in the development of 7 bean lines (coded BRU 3- 10) with intermediate to high levels of resistance to Acanthoscelides obtectus and Zabrotes subfasciatus. Concerning A. godmani, a preliminary Apion nursery (2 replications) was carried out with 198 lines selected from the 1984 red and black adaptation nurseries. (CIAT)